Effect of Allium sativum and fish collagen on the proteolytic and angiotensin-I converting enzyme-inhibitory activities in cheese and yogurt - Shori, A.B.; Baba, A.S.; Keow, J.N. (2012)
There is an increasing demand of functional foods in developed countries. Yogurt plays an important role in the management of blood pressure. Several bioactive peptides isolated from Allium sativum or fish collagen have shown antihypertensive activity. Thus, in the present study the effects of A. sativum and/or Fish Collagen (FC) on proteolysis and ACE inhibitory activity in yogurt (0, 7 and 14 day) and cheese (0, 14 and 28 day) were investigated. Proteolytic activities were the highest on day 7 of refrigerated storage in A. sativum-FC-yogurt (337.0 +/- 5.3 microg g(-1)) followed by FC-yogurt (275.3 +/- 2.0 microg g(-1)), A. sativum-yogurt (245.8 +/- 4.2 microg g(-1)) and plain-yogurt (40.4 +/- 1.2 microg g(-1)). On the other hand, proteolytic activities in cheese ripening were the highest (p < 0.05) on day 14 of storage for plain and A. sativum-cheeses (411.4 +/- 4.3 and 528.7 +/- 1.6 microg g(-1), respectively). However, the presence of FC increased the proteolysis to the highest level on day 28 of storage for FC- and A. sativum-FC cheeses (641.2 +/- 0.1 and 1128.4 +/- 4.5 microg g(-1), respectively). In addition, plain- and A. sativum-yogurts with or without FC showed maximal inhibition of ACE on day 7 of storage. Fresh plain- and A. sativum-cheeses showed ACE inhibition (72.3 +/- 7.8 and 50.4 +/- 1.6 % respectively), the presence of FC in both type of cheeses reduced the ACE inhibition to 62.9 +/- 0.8 and 44.5 +/- 5.0%, respectively. However, refrigerated storage increased ACE inhibition in cheeses (p < 0.05 on day 28) in the presence of FC more than in the absence. In conclusion, the presence of FC in A. sativum-yogurt or cheese enhanced the proteolytic activity. Thus, it has potential in the development of an effective dietary strategy for hypertension associated cardiovascular diseases.